Students ’ Views on Learning Environment for Undergraduate Mathematics in Selected Higher Learning Institutions in Tanzania - Likinjiye, Morwo Likinjiye; Kanukisya, Blackson Kanukisya; Ndabi, Joyce Ndabi (Papers in Education and Development, 2023)
Abstract The aim of this paper is to find out views of students on learning environment for undergraduate mathematics in Tanzania. 303 male and 120 female undergraduate students participated in the study. Data were collected through questionnaire and interview methods. Students ' views were positive on lecturers ' characteristics, academic relationships, as well as gender sensitivity in the learning environment. However, the students had a concern on the teaching methods for the subject, the nature of tests during their coursework, as well as marking and grading styles. This paper concludes that, among others, contrary to observations in non-mathematics contexts, male and female students hold similar views on many aspects of the learning environment for undergraduate mathematics. However, these views depended on the mode of students ' participation in the subject. Keywords gender, gender sensitivity, lecturers ' characteristics, undergraduate, post-compulsory mathematics